Copayment and recommended strategies to mitigate its impacts on access to emergency medical services under universal health coverage: a case study from Thailand - Paibul Suriyawongpaisal; Wichai Aekplakorn; Samrit Srithamrongsawat; Chaisit Srithongchai; Orawan Prasitsiriphon; Rassamee Tansirisithikul (BMC, 2016)
Abstract Background Although bodies of evidence on copayment effects on access to care and quality of care in general have not been conclusive, allowing copayment in the case of emergency medical conditions might pose a high risk of delayed treatment leading to avoidable disability or death. Methods Using mixed-methods approach to draw evidence from multiple sources (over 40,000 records of administrative dataset of Thai emergency medical services, in-depth interviews, telephone survey of users and documentary review), we are were able to shed light on the existence of copayment and its related factors in the Thai healthcare system despite the presence of universal health coverage since 2001. Results The copayment poses a barrier of access to emergency care delivered by private hospitals despite the policy proclaiming free access and payment. The copayment differentially affects beneficiaries of the major 3 public-health insurance schemes hence inducing inequity of access. Conclusions We have identified 6 drivers of the copayment i.e., 1) perceived under payment, 2) unclear operational definitions of emergency conditions or 3) lack of criteria to justify inter-hospital transfer after the first 72 h of admission, 4) limited understanding by the service users of the policy-directed benefits, 5) weak regulatory mechanism as indicated by lack of information systems to trace private provider's practices, and 6) ineffective arrangements for inter-hospital transfer. With demand-side perspectives, we addressed the reasons for bypassing gatekeepers or assigned local hospitals. These are the perception of inferior quality of care and age-related tendency to use emergency department, which indicate a deficit in the current healthcare systems under universal health coverage. Finally, we have discussed strategies to address these potential drivers of copayment and needs for further studies.